Importance of Vestibulo-ocular Reflex Gain and Refixation Saccade Analysis in Individuals with Auditory Neuropathy Spectrum Disorder - Sinha, Sujeet Kumar; Neupane, Anuj Kumar; Gururaj, Krithika (International Archives of Otorhinolaryngology, 2020)
Introduction Auditory neuropathy spectrum disorder (ANSD) features the presence of otoacoustic emissions, poor speech identification score and absent auditory brainstem response.Objective The present study was designed to evaluate the functioning of all six semicircular canals in individuals with ANSD and to compare it with those of normal-hearing individuals.Methods A total of 50 individuals participated in the present study, in which Group I comprised 25 normal-hearing individuals, and Group II comprised 25 individuals with ANSD. All of the participants underwent case history, pure tone audiometry, immittance, otoacoustic emissions, auditory evoked response and video head impulse test (vHIT).Results The independent sample t-test revealed significantly lower vestibulo-ocular reflex gain values in individuals with ANSD. A presence of 100% corrective refixation saccades was observed in the same group. The Pearson correlation test revealed no significant correlation between vestibulo-ocular reflex (VOR) gain with duration of hearing loss and pure tone thresholds for any of the three orthogonal planes. The chi-squared test revealed no association between the VOR gain values and the presence or absence of saccades in any of the semicircular canals (p > 0.05).Conclusion Huge percentages of individuals with ANSD have been found to have associated vestibular dysfunction as well. Therefore, the vHIT can be used as one of the important tests of the vestibular test battery to evaluate all six semicircular canals in individuals with ANSD.
Keywords: auditory neuropathy; semicircular canals; vestibulo-ocular reflexes; saccades; pure tone threshold